Cracking evaluation of micro steel fibre (MSF) concrete by utilising acoustic emission signal method - Ramasamy, Suchitra (2022)
Concrete is one of the world’s most widely used construction material. However, it is known that concrete is a brittle composite which is sensitive to cracking. Hence, this study was conducted to enhanced the mechanical properties of concrete and to monitor the cracking activities through acoustic emission (AE) technique. The main additional material used in this research was micro steel fibres (MSF) with a volume fraction of 0%, 0.5%, 0.75%, 1.00% and 1.25%. At the earliest stage, the mechanical properties (e.g. compressive strength test, splitting tensile test and modulus of elasticity) was determine. Next, a series of prisms were made to carry out acoustic emission (AE) signal analysis. From the data analysis, the highest compressive strength of 74.50 MPa was obtained by a concrete specimen containing 1.25% MSF at the age of 28 days. The very same specimen achieved the highest splitting tensile strength and modulus of elasticity at 5.96 MPa and 49.47 GPa, respectively. The presence of 0.5% MSF for both specimens aged for 7 and 28 days had a signal strength of 3.6 × 109 pVs and 4.0 × 109 pVs, respectively. Meanwhile, the maximum readings of absolute energy were obtained by specimens containing 0.5% and 1.00% of MSF at 8.0 × 109 aJ and 9.0 × 109 aJ, respectively. In addition, the highest amplitude value gained from this study is 99dB. From the RA value analysis, it can be concluded that the concrete specimen failed through tensile cracking. In a nutshell, the higher the presence of MSF in a concrete composite, the higher its strength. Meanwhile, the highest signal strength and absolute energy prove that the specimens have better resistance towards cracking. Moreover, the RA value analysis is appropriate for concrete crack classification. Therefore, the AE technique is found to be suitable for crack evaluation and monitoring methods.